Frazeološke konstrukcije – teoretični in leksikografski vidik - Ulčnik, Natalija (Slavistična revija, 2025)
The article discusses the phraseme constructions (e.g. X of all X, X is not Y). Recent phra seological studies pay considerable attention to this topic under the influence of construction grammar, but such research has not received significant attention in the field of Slovene studies. The article provides a theoretical background for researching these phraseological units based on a model syntactic structure, highlights their definitional characteristics and correlation to related units, and analyses the inclusion of such elements in Slovene lexicographic sources.
Keywords: construction grammar; frazeologija; konstrukcijska slovnica; lektikografija; lexicography; model syntactic structure; modelna skladenjska zgradba; phraseology